Memperkenalkan Sejarah Pahlawan Nasional K.H Agus Salim bagi Peserta Didik MI/SD di Indonesia - Farahin Aisah Farhat, Putri Nur; Fuadah Z, Anis (STAINU Purworejo, 2020)
The history of national heroes is very useful for students, namely students can imitate and emulate the attitudes and nature of national heroes. One of the national heroes who should be emulated and exemplified is KH Agus Salim, many of his attitudes and traits are exemplary and exemplary by today's students, including his being smart and intelligent, obedient and obedient to the religion he follows, having thoughts and extensive knowledge, proficient in foreign languages, disciplined and responsible. Weak children's knowledge about the history of national heroes, is an important concern for education. So it is very important for the nation's children to have self-awareness on the purpose of learning history, so that they can recall the struggles of the nation's founders in seizing Indonesia's extraordinary independence, and be able to appreciate every hero who was willing to fight for Indonesian independence. This article was written with the aim of introducing the history of national hero K.H Agus Salim to MI / SD students in Indonesia, with interactive learning methods between teachers and students so as to make history lessons not boring. This writing method uses a critical historical method, with stages (1) object selection, (2) Heuristics (determining the source of its history), (3) Criticism (studying historical sources). This journal is written about the discussion about the role of KH Agus Salim in national history while aiming to introduce KH Agus Salim as a national hero with related discussion material: 1) introducing (biography) national hero KH Agus Salim, 2) revealing the values of struggle (organization / independence process) national heroes, 3) introduction of heroic values to students in MI / SD in Indo